Factors Inhibiting Land And Building Taxpayer Compliance In Sei Sikambing B Village, Medan Sunggal - Afrida Yani Siahaan; Nurhalizah Nurhalizah; Vinka Atira Werdy; Galih Supraja (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Land and Building Tax (PBB) serves as a vital source of regional revenue, supporting essential government initiatives such as infrastructure development, education, healthcare, and various public services. Despite its importance, community compliance with PBB payments in Sei Sikambing B Sub-district remains low. This raises the need to identify the factors hindering compliance and explore strategies to address them. This study aims to uncover the challenges affecting PBB payment compliance and assess the effectiveness of government measures in raising public awareness. A qualitative approach was employed, involving data collection through interviews with residents and staff from the Sei Sikambing B Village office. The findings reveal several key obstacles to taxpayer compliance, including limited public awareness, inadequate enforcement of tax regulations, financial constraints, insufficient dissemination of tax-related information, and inefficiencies in the tax collection system.